THE INFLUENCE OF ESG DISCLOSURE SCORE ON THE COST OF CAPITAL IN THE MANUFACTURING COMPANY - Sidi Rai, Ni Made Gianti Dirdasih; Ismawati, Anastasia Filiana (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2024)
This study examines the relationship of ESG disclosure score to the cost of capital. ESG disclosure score is proxied individually, namely environmental disclosure score, social disclosure score and governance disclosure score taken from Refinitiv. The cost of capital in this study is proxied by the cost of debt and equity. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2021. Data collection using secondary data comes from annual reports and ESG disclosure scores from Refinitiv and data analysis using multiple linear regression with the help of Stata software version 17. The results state that the environmental and social disclosure score has no significant effect on the cost of equity. The governance disclosure score has a significant negative effect on equity costs. The environmental and governance disclosure score has no significant effect on the cost of debt. Social disclosure score has a significant negative effect on the cost of debt.